Reciprocity and market economy in the Andean peasant community: The example of Yucay - Fioravanti, Antoinette (1973)
The current process of the Peruvian Agrarian Reform accelerates the influence of the market economy on the peasant communities of the Andes. Increasingly, peasants are distinguished according to their access to the means of production and their way of life: new social structures are appearing while the traditional oppositions between landowner and peasant, "white" and "Indian", hacienda and Community are disappearing. Traditional groups, defined until recently by kinship, are now being distributed into classes of unequal wealth. However, old forms of production and ideologies linked to previous models continue to function. It is not about survival but rather an Andean way of integrating into the market without completely abandoning traditional reciprocity, a simple manifestation of the praxis of the Andean people.